Polyketide β-branching: diversity, mechanism and selectivity. Issue 4 (15th October 2020) - Walker, P. D.; Weir, A. N. M.; Willis, C. L.; Crump, M. P.
Abstract : The structural diversity of newly discovered polyketides continues to grow. This review summarises the range of structures with single and multiple β-branches and the mechanistic details of each catalytic step, covering literature from 2008 to August 2020. Abstract : Covering: 2008 to August 2020 Polyketides are a family of natural products constructed from simple building blocks to generate a diverse range of often complex chemical structures with biological activities of both pharmaceutical and agrochemical importance. Their biosynthesis is controlled by polyketide synthases (PKSs) which catalyse the condensation of thioesters to assemble a functionalised linear carbon chain. Alkyl-branches may be installed at the nucleophilic α- or electrophilic β-carbon of the growing chain. Polyketide β-branching is a fascinating biosynthetic modification that allows for the conversion of a β-ketone into a β-alkyl group or functionalised side-chain. The overall transformation is catalysed by a multi-protein 3-hydroxy-3-methylglutaryl synthase (HMGS) cassette and is reminiscent of the mevalonate pathway in terpene biosynthesis. The first step most commonly involves the aldol addition of acetate to the electrophilic carbon of the β-ketothioester catalysed by a 3-hydroxy-3-methylglutaryl synthase (HMGS). Subsequent dehydration and decarboxylation selectively generates either α, β- or β, γ-unsaturated β-alkyl branches which may be further modified. This review covers 2008 to August 2020 and summarises the diversity of β-branch incorporation and the mechanistic details of each catalytic step. This is extended to discussion of polyketides containing multiple β-branches and the selectivity exerted by the PKS to ensure β-branching fidelity. Finally, the application of HMGS in data mining, additional β-branching mechanisms and current knowledge of the role of β-branches in this important class of biologically active natural products is discussed.